Non-invasive assessment of the cardiac effects of Chironex fleckeri and Carukia barnesi venoms in mice, using pulse wave doppler. (15th October 2020) - Seymour, Jamie; Saggiomo, Silvia; Lam, Willis; Pereira, Peter; Little, Mark
Abstract: Both Chironex fleckeri venom (CFV) and Carukia barnesi venoms (CBV) are known to cause significant cardiac morbidity and mortality. Many animal studies have demonstrated cardiac dysfunction with these venoms. This study specifically examines the systolic and diastolic cardiac functions using non-invasive pulse wave doppler. Mitral and aortic doppler sonograms of anaesthetised mice were obtained utilising a 10 MHz doppler probe. These continuous sonograms were analysed to ascertain changes in cardiac function before and after the parenteral administration of the test venoms. We found that CFV administration causes rapid cardiac dysfunction without a change in heart rate. Analysis of the resulting sonograms shows both systolic and diastolic dysfunction which together is suggestive of a progressively poorly compliant, contracted left ventricle. Additionally, the rapidity of cardiac dysfunction suggests a direct effect of CFV on myocardial cells. In contrast CBV showed a moderate immediate inotropic and chronotropic effect that was sustained until precipitous cardiac decompensation. This is consistent with the hypotheses of a toxin induced stress cardiomyopathy from sustained catecholaminergic activity. Highlights: Chironex fleckeri venom (CFV) was associated with a rapid deterioration in cardiac output. Our findings show that CFV causes a measurable progressive systolic and diastolic dysfunction. This suggest a progressively poorly compliant ventricle, possibly contracted. Carukia barnesi venom (CBV), caused an increase in HR and inotropy until precipitous cardiac failure. This is consistent with what one might expect of a stress induced cardiomyopathy like Takotsubo.